Phase 1 oncology trials and informed consent. Issue 12 (17th November 2012) - Miller, Franklin G; Joffe, Steven
Abstract : Ethical concerns have been raised about the quality of informed consent by participants in phase 1 oncology trials. Interview surveys indicate that substantial proportions of trial participants do not understand the purpose of these trials—evaluating toxicity and dosing for subsequent efficacy studies—and overestimate the prospect of therapeutic benefit that they offer. In this article we argue that although these data suggest the desirability of enhancing the process of information disclosure and assessment of comprehension of the implications of study participation, they do not necessarily invalidate consent by phase 1 trial participants.